Physical and chemical properties of a lipase-transesterified palm stearin/palm kernel olein blend and its isopropanol-solid and high melting triacylglycerol fractions - Chu, B.S.; Ghazali, H.M.; Lai, O.M.; Che Man, Y.B.; Yusof, S. (Elsevier, 2002)
Palm stearin and palm kernel olein at 1:1 (w/w) ratio was transesterified using 1.0% w/w lipase from Rhizomucor miehei (Lipozyme IM60, Novo Nordisk). The transesterified blend, as well as its isopropanol-solid (fat solid fractionated using isopropanol at 5 °C) and high melting glycerides (HMG, fat solid fractionated using acetone at 10 °C) were studied. Low carbon number triacylglycerols (TG), ranging from C32 to C38, and high carbon number TG (C48 and C50) were used to produce TG ranging from C40 to C46. Transesterification did not much alter the fatty acid (FA) composition of the mixture, but it increased the level of C12:0 (lauric acid) and reduced the C16:0 (palmitic acid) level in the isopropanol-solid and HMG fractions compared to the control. Transesterification also did not much alter the polymorphic forms of the mixture. However, the HMG fraction of the transesterified mixture had more tendency to form β' crystals than the control. Slip melting point of transesterified fat was lower than the control. Heating thermograms of differential scanning calorimetry (DSC) illustrated that the high-melting TG peaks in the transesterified blend were reduced in size while the low-melting TG peaks were broadened, mainly due to the rearrangement of FA to form lower-melting TG. The temperature of the high-melting TG peaks of all samples showed a good correlation (correlation coefficient, r=0.9899; P<0.05) with PPP (P, palmitic acid) levels. Formations of low-melting TG also broadened the low-temperature (low-T) peak in the cooling curve of DSC and reduced the crystallisation temperature of the low-T peak. The high-temperature (high-T) peak of the cooling curves were more dominant in the isopropanol-solid and HMG fractions of both transesterified and control blends. The high-T peaks of the transesterified blend was broader and had a lower temperature than the control. Transesterified blends had lower solid fat contents (SFC) than the control at all temperatures. Production of more low-melting TG in the transesterified blend caused a sharp drop in SFC of the control which shifted from the range of 15-20 °C to 10-15 °C.